Attention bias modification training under working memory load increases the magnitude of change in attentional bias - Clarke, Patrick; Branson, S.; Chen, N.; Van Bockstaele, B.; Salemink, E.; MacLeod, C.; Notebaert, L. (Elsevier BV; North Holland, 2017)
© 2017 Elsevier LtdBackground and objectives Attention bias modification (ABM) procedures have shown promise as a therapeutic intervention, however current ABM procedures have proven inconsistent in their ability to reliably achieve the requisite change in attentional bias needed to produce emotional benefits. This highlights the need to better understand the precise task conditions that facilitate the intended change in attention bias in order to realise the therapeutic potential of ABM procedures. Based on the observation that change in attentional bias occurs largely outside conscious awareness, the aim of the current study was to determine if an ABM procedure delivered under conditions likely to preclude explicit awareness of the experimental contingency, via the addition of a working memory load, would contribute to greater change in attentional bias. Methods Bias change was assessed among 122 participants in response to one of four ABM tasks given by the two experimental factors of ABM training procedure delivered either with or without working memory load, and training direction of either attend-negative or avoid-negative. Results Findings revealed that avoid-negative ABM procedure under working memory load resulted in significantly greater reductions in attentional bias compared to the equivalent no-load condition. Limitations The current findings will require replication with clinical samples to determine the utility of the current task for achieving emotional benefits. Conclusions These present findings are consistent with the position that the addition of a working memory load may facilitate change in attentional bias in response to an ABM training procedure.